Пориста структура порошків нанорозмірного боразографену - Petrova, A. V.; Garbuz, V. V.; Lobunets, T. F.; Tomila, T. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2017)
The structural features of surface of the nano-dimensional bor-azo-graphenic powders (t-BNg) after previous washing in boiling water were researched. The results showed that after process of purifier (washing) the powder’s surface of t-BNg characterized as slit-like micro-, mesoporous (monodispersed) structure with a narrow porous distribution in the range of 3.82 - 4.17 nm. The outer surface specific area of the powders of t-BNg according to “t - method” is 28.3 m2/g. The inner specific surface area of the mesopores is 141 m2/g (BJH method). The residues of boron oxonitride in the form of a purified sublimate, a white powder, extracted from a washed and dried sample of t-BNg at a temperature of 540 K and a pressure of ≤ 1.0 Pa. The sublimate, according to chemical analysis and infrared spectroscopy, was identified on the assumption of the cyclic dimer of di-hydro-di-hydroxo-di-bor-ox-azole of the composition of H(OH)[(BON)2](OH)H. The model of carbamide synthesis of boron nitride, as a sequence of chemical transformations of borate-carbamide precursors in a freely radical boron-pair (> B - N <), have proposed.